PAIN ASSOCIATED WITH INTRAOSSEOUS ANESTHESIA WITH QUICKSLEEPER AND POST-OPERATIVE CONDITION OF THE PERFORATION SITE - Emiliya Simeonova; Elena Boyadzhieva; Valeriya Aleksandrova; Snezhana Tsanova (Peytchinski Publishing, 2023)
Purpose: The aim of the study is to determine the pain during intraosseous anesthesia (IA) with the Quicksleeper and the post-operative state of the perforation site. Materials and methods: The subjects of the study were 58 patients who underwent successful intraosseous analgesia, indicated with treatment of caries or irreversible pulpitis of mandibular first and second molars. The Visual Analogue Scale was used to assess the pain during the perforation of the compact bone and during the infiltration of anesthetic solution into the cancellous bone. All 58 patients were followed up at the 24th hour and on the 7th day after the manipulation, and the following parameters were evaluated: condition of the perforation site and presence of palpation pain. Results: Only 10 patients registered mild pain during perforation of compact bone and 8 - during anaesthetic infiltration. At 24 hours after IA, 12 patients registered mild pain, 6 patients registered moderate pain at the perforation site. On the 7th day, we established mild pain in 4 patients. After IA a reactive inflammatory process was registered in 27% of the cases at 24 hours, while on the 7th day, the inflammatory reaction was registered in only 6% of the cases. Conclusion: The intraosseous system Quicksleeper allows painless perforation of the compact bone and infiltration of the anesthetic solution into the cancellous bone due without risk of serious post-operative complications at the site of anesthesia.